Drilling Toward Fluency: Effects of the Audio-Lingual Method on Grade-VII Arabic Speaking at State Islamic Junior High School - Yustika Ayu Rahma; Ade Irma (Fakultas Tarbiyah dan Keguruan, 2025)
Purpose – This study examined how the Audio-Lingual Method (ALM) is implemented and how it affects Arabic speaking skills among seventh-grade learners at State Islamic Junior High School (MTsN) 5 Pandeglang. Design/methods/approach – Using a quasi-experimental nonequivalent control group design with intact classes (experimental n=20; control n=20), we administered a pretest–treatment–posttest sequence contrasting ALM-based instruction with routine instruction under natural classroom conditions. Speaking performance was assessed with standardized prompts and an analytic checklist, and scores were analyzed with assumption-checked inferential tests and effect sizes. Findings – The experimental class improved from 48.64 to 81.36 (mean gain = 32.73), while the control class rose from 55.00 to 68.64 (mean gain = 13.64), producing a between-group gain difference of 19.09 points in favor of Hot Seat. These results indicate that structured role rotation, calibrated questioning, and rapid formative feedback can substantially increase both the quantity and quality of meaningful oral turns within equivalent instructional time. Future research should employ paired or mixed-effects designs with baseline covariate adjustment, include delayed and far-transfer outcomes, explore Audio-Lingual Method combined with brief communicative tasks, and investigate dose–response and cost-effectiveness to inform scalable implementation. Collectively, the evidence supports retaining Audio-Lingual Method as a core habit-formation routine while integrating targeted communicative practice to bolster spontaneous interaction. Research implications – The large, distribution-shifting effects observed suggest that habit-formation pedagogies such as the Audio-Lingual Method merit renewed theoretical and empirical attention in junior-secondary Arabic. Future studies should test Audio-Lingual Method as a core routine combined with brief communicative tasks, use individual-level models (e.g., mixed effects/ANCOVA), and include delayed and far-transfer outcomes to establish durability and generalizability. Dose–response and cost-effectiveness analyses are further needed to guide scalable implementation in resource-variable schools.